Is the Welfare State Self-destructive? A Study of Government Benefit Morale - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Assar Lindbeck has pointed to the problem that generous welfare state institutions may in the long-run undermine those social norms which limit the costs and incentives effects of the welfare state and thus guarantee its viability. This study is the first to assess the empirical validity of Lindbeck?s notion by assessing the long-run link between the welfare state and social norms with regard to the honest take-up of government benefits. Based on the results of four waves of the World Value Surveys the determinants of benefit morale – defined as the reluctance to claim government benefits without legal entitlement – are analysed. Besides a standard list of the respondents? individual characteristics, macroeconomic indicators describing a country?s long-run welfare state and labour market history are included. The results support the empirical validity of Lindbeck?s theory: An increase of government benefits and unemployment is in the long-run associated with deteriorating welfare state ethics.
Keywords: Z13; I38; I30; 330; benefit morale; tax morale; welfare state reforms